Instagram Sebagai Media Informasi untuk Memperkenlakan Keberadaan dan Kegiatan dalam Komunitas @Pf_Ent Palembang - Irawan, Andre; Wijayani, Isna (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
PF Entertainment is a community of lovers of Korean-style modern dance or Korean Dance Cover which uses the mass media Instagram as an information medium for the public to introduce their existence and activities. However, as time goes by, this media competes with other media such as TikTok, which is currently very popular. The aim of this research is to utilize knowledge of Instagram media in introducing the existence and activities of PF Entertainment. This study uses a qualitative method. The theory used is Effective Communication Techniques. The result of this research is that by using Instagram, of course the admin always updates the activities carried out with 2 to 7 pieces of information in one month so that followers can follow and find out about developments in the PF Entertainment community.